Effects of microbubbles in precoat filtration - Ubukata, Hikaru; Yagishita, Koichi; Kitagawa, Tominori; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2014)
When the diameter of a microscopic bubble is less than 50 μm, it is referred to as microbubble (MB). The properties of MB are different from those of bubbles whose diameter is more than 50 μm. For instance, MB has the negatively charged surface and the self-pressurization effect. Because of these properties of MB, it is used in some processes such as wastewater treatment or aquatic environmental remediation. It has been reported that when diluted slurry of FeO(OH) is filtered in precoat layer containing MB at a constant rate, the filtration time becomes more than twice longer compared to that of conventional precoat filtration. This technique can decrease the frequency of filter medium cleaning and reprecoating, resulting in a cost reduction of precoat filtration. However, it has not been clarified why the addition of MB to the precoat layer lengthen the filtration cycle. In this study, we discuss the effects of MB on precoat layer prepared by MB body feeding to kieselguhr slurry.